Diagnosis of scar endometriosis on aspiration cytology and cellblock: Myth or reality. Issue 3 (17th November 2021) - Varshney, Bharti; Bharti, Jyotsna Naresh; Satyendra, Boddeda Tulasi; Singh, Pratibha
Abstract: Endometriosis is defined as the presence of endometrial tissue outside the uterus. It can occur both in the pelvic and extra pelvic regions. Abdominal scar endometriosis is a rare type of extra pelvic endometriosis that occurs after surgery involving the uterus. In the post‐cesarean section, the development of scar endometriosis is a rare event and the diagnosis of scar endometriosis is usually confirmed after surgical excision and histopathological examination. We present a case of an abdominal lump in a 26‐year‐old female with a myriad of clinical differential diagnoses, which was rendered a confirmed diagnosis of scar endometriosis with the help of fine‐needle aspiration cytology and cell block aided with immunohistochemistry.